Buffaloes are ‘Black Gold’ not Black Cows - Priya; Meeti Punetha; Pradeep Kumar; P S Yadav; Dharmendra Kumar (Animal Reproduction Update, 2024)
Buffalo and cow, both are vital to global agricultural landscapes; possess distinct traits that shape their roles in farming. Despite belonging to the Bovidae family, buffaloes excel in resilience and adaptability to harsh environments, while cows thrive in temperate climates. Their evolutionary history reveals separate domestication events, with buffaloes originating later, around 3,000–7,000 years ago. Their chromosome numbers and breeding patterns reflect their genetic differences. Anatomically, buffaloes exhibit unique digestive, reproductive, and thermoregulatory adaptations, influencing productivity. Buffalo milk, richer in fat and solids, surpasses cow milk in nutritional value, driving its prominence in global dairy markets. FAO data indicates a notable surge in buffalo milk production, outpacing that of cows global. This perspective review discusses the diverse benefits of buffalo and highlights the importance of distinguishing between buffaloes and cows in order to comprehend their crucial contributions to agricultural livelihoods and global culinary traditions.